An empirical investigation of International Fisher Effect on 10 Asean countries - Alizadeh, Hossein Nezakati; Md Nassir, Annuar; Sheikh Abou Masoudi, Sayed Yousef (Asian Network for Scientific Information, 2014)
In this study the empirical evidence of International Fisher Effect is investigated among ASEAN member countries and assuming Malaysia as the home country. In general the results of this study indicated that exchange rates movements do not follow the International Fisher Effect theory and nominal interest rate differentials cannot completely offset the currency value changes among ASEAN countries in the long run except the fact that this theory is partially held in Malaysia-Indonesia case for the surveyed period.